Comparison of Different Risk Scores for Predicting Contrast Induced Nephropathy and Outcomes After Primary Percutaneous Coronary Intervention in Patients With ST Elevation Myocardial Infarction - Liu, Yuan-hui; Liu, Yong; Zhou, Ying-ling; He, Peng-cheng; Yu, Dan-qing; Li, Li-wen; Xie, Nian-jin; Guo, Wei; Tan, Ning; Chen, Ji-yan (The American journal of cardiology, 2016)
Accurate risk stratification for contrast-induced nephropathy (CIN) is important for patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI). We aimed to compare the prognostic value of validated risk scores for CIN. We prospectively enrolled 422 consecutive patients with STEMI undergoing PPCI. Mehran; Gao; Chen; age, serum creatinine (SCr), or glomerular filtration rate, and ejection fraction (ACEF or AGEF); and Global Registry for Acute Coronary Events risk scores were calculated for each patient. The prognostic accuracy of the 6 scores for CIN, and in-hospital and 3-year all-cause mortality and major adverse clinical events (MACEs), was assessed using the c-statistic for discrimination and the Hosmer–Lemeshow test for calibration. CIN was defined as either CIN-narrow (increase in SCr ≥0.5 mg/dl) or CIN broad (≥0.5 mg/dl and/or a ≥25% increase in baseline SCr). All risk scores had relatively high predictive values for CIN-narrow (c-statistic: 0.746 to 0.873) and performed well for prediction of in-hospital death (0.784 to 0.936), MACEs (0.685 to 0.763), and 3-year all-cause mortality (0.655 to 0.871). The ACEF and AGEF risk scores had better discrimination and calibration for CIN-narrow and in-hospital outcomes. However, all risk score exhibited low predictive accuracy for CIN-broad (0.555 to 0.643) and 3-year MACEs (0.541 to 0.619). In conclusion, risk scores for predicting CIN perform well in stratifying the risk of CIN-narrow, in-hospital death or MACEs, and 3-year all-cause mortality in patients with STEMI undergoing PPCI. The ACEF and AGEF risk scores appear to have greater prognostic value.